Supporting children and young people in schools : a guide for foundation degree students - Tatton, Allison; Bright, Clare; Thomas, Lorraine, 1961- (Routledge, 2018)
"This book explores the diverse ways in which practitioners can support students' learning, enabling them to develop and flourish in the school setting. Chapters bring together various theoretical approaches, draw on case studies from practice, and foreground the concrete ways in which practitioners might respond to the specific needs of children. Maintaining a strong link with current policy and curricula, each chapter takes a detailed and nuanced approach to a different aspect of pupil support, whilst reflective questions, activites and suggestions for further reading encourage the reader to reflect, re-consider and delve deeper into key topics. Areas addressed include: - theories of child and adolescent development - managing student behaviour and building positive relationships - working with pupils with special educational needs - making use of assessment and evaluation - furthering professional skills and career progression. An accessible yet comprehensive guide to a wide range of key issues, this book will provide Foundation Degree students, Teaching Assistants, and practitioners working in a range of educational settings with essential support as they progress from study into practice"- Resumé vydavatel
Keywords: výchova a vzdělávání; základní vzdělávání; středoškolské studium; integrovaná výchova a vzdělávání; education; elementary school education; secondary education; integrated education; metodické příručky; elektronické knihy; methodological manuals; electronic books